Growth and otolith morphology of the Cape hakes Merluccius capensis (Cast.) and M. paradoxus (Franca) - Botha, Louis,1940- (Stellenbosch : Stellenbosch University, 2012)
Thesis (M. Sc.) -- University of Stellenbosch, 1970.